Twelfth Night, or What You Will - Shakespeare, William; Edited By Roger Warren and Stanley Wells (New York Oxford University Press, 1998)
In the modern theater, Twelfth Night is one of the most popular of Shakespeare's plays, and this edition places particular emphasis on its theatrical qualities in both the introduction and the full and detailed commentary. Where original music has not survived, James Walker has composed settings compatible with the surviving originals, freshly edited so that this edition, unique among modern editions, offers all the music required to perform the play. It will be invaluable to actors, directors, and students at all levels.
Include Index, Appendix, References and Abbrevations.
The arrival of shipwrecked twins in the land of Illyria creates havoc in this comical story of love in disguise.
Keywords: Twins -- Twelfth Night (Shakespeare, William)